Identifikasi Pembelajaran Seni Berbasis Budaya Lokal Yogyakarta Pada Anak Usia 5-6 Tahun Di TK ABA Jetis Argomulyo Daerah Istimewa Yogyakarta - W, Yourma Osnithia; Pamungkas , Joko (JURNAL ILMU PENDIDIKAN, 2022)
Early childhood has the potential for interests and talents that children have at different stages of development. One of them is through art activities that have many benefits for children to distinguish each meaning in thinking by feeling with the benefits that can be obtained in learning art. One of the art activities that can be done at school is to introduce traditional Yogyakarta dances and angklung games. Yogyakarta's local cultural wisdom is one of the efforts that can preserve local culture for early childhood. Through art activities based on local cultural wisdom, Yogyakarta can explore children's abilities well so that children can express, play and participate in preserving local cultural wisdom.